2018
DOI: 10.17511/ijpr.2018.i02.08
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Kangaroo Mother care for low birth weight babies: supportive factors and barriers perceived by mothers

Abstract: Introduction: Kangaroo mother care (KMC) consist of prolonged skin to skin contact between mother and infant and exclusive breastfeeding. It was originally developed to prevent hypothermia and to enhance bonding between mother and Infant. Methods: It was a questionnaire based cross sectional observational study. Questionnaire was prepared by authors in local native language and was validated by experts; mothers with babies fit for KMC were enrolled and interviewed with a predefined proforma having both open an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Heidarzadeh M et al in a study in Iran [13] showed that the duration of KMC was at least 1-3 h which was repeated at least three times a day. Another study by Mekle D et al [14] in India revealed that >1 h KMC was practiced per sitting in 56% studied newborns (n=50) and >4 h/day KMC was practiced in 14% which was similar to our study result where the mean duration of KMC was 2.3 h per shift and 7 h/day(n=50).…”
Section: Discussionsupporting
confidence: 90%
“…Heidarzadeh M et al in a study in Iran [13] showed that the duration of KMC was at least 1-3 h which was repeated at least three times a day. Another study by Mekle D et al [14] in India revealed that >1 h KMC was practiced per sitting in 56% studied newborns (n=50) and >4 h/day KMC was practiced in 14% which was similar to our study result where the mean duration of KMC was 2.3 h per shift and 7 h/day(n=50).…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4] Despite its proven benefits, the intervention has not been fully integrated into health-care systems and average duration of KMC remains low due to various barriers. [5][6][7][8] KMC in twins can be challenging for the parents especially in resource-limited settings. 9,10 Twin/ multiple pregnancy rates have increased in the recent years due to increasing maternal age and use of assisted reproductive technology.…”
mentioning
confidence: 99%
“…KMC alleviates stress and anxiety in the mother, strengthens parent‐infant bonding and results in better neurodevelopment outcomes 1–4 . Despite its proven benefits, the intervention has not been fully integrated into health‐care systems and average duration of KMC remains low due to various barriers 5–8 . KMC in twins can be challenging for the parents especially in resource‐limited settings 9,10 .…”
mentioning
confidence: 99%